The serpent's secrets - Downer, John; Cradock, Colin; Attenborough, David, 1926- (London : BBC Enterprises, 1982)
The world of snake has been bound up with prejudice and legend that, until recently, it has been hard to extract fact from fiction. But in this documentary advanced filming techniques are used to examine almost every aspect of snake behavior. As the camera explores its silent and private world a unique view of the serpent's way of life is revealed. The highlights of this fascinating film are the intriguing mating rituals, the birth of an adder and, in slow motion, an adder strike- from the mouse's point of view.
Backup available in VHS 1/2 in.
Keywords: Serpents -- Behavior; Snakes -- United Kingdom